Causal effect of vascular endothelial growth factor on the risk of atrial fibrillation: a two-sample Mendelian randomization study - Han, Siliang; Xue, Ling; Chen, Chunhong; Xie, Junmin; Kong, Fanchang; Zhang, Fang (Frontiers in Cardiovascular Medicine, 2024)
Background Observational studies have found that vascular endothelial growth factor (VEGF) levels are associated with the risk of cardiovascular disease. However, it remains unclear whether VEGF levels have a causal effect on the risk of atrial fibrillation. Methods A two-sample Mendelian randomization (MR) study was conducted to explore the causal relationship between VEGF levels and the risk of atrial fibrillation. Genetic variants associated with VEGF [VEGF-A, VEGF-C, VEGF-D, VEGF receptor−2 (VEGFR-2), VEGFR-3] and atrial fibrillation (atrial fibrillation, atrial fibrillation and flutter) were used as instrumental variables. Data on genetic variants were obtained from published genome-wide association studies (GWAS) or the IEU Open GWAS project. Inverse-variance weighted (IVW) analysis was used as the primary basis for the results, and sensitivity analyses were used to reduce bias. Causal relationships were expressed as odds ratio (OR) with 95% confidence interval (CI), and a P-value of <0.1 corrected for False Discovery Rate (FDR) (PFDR < 0.1) was considered to have a significant causal relationship. Results Genetically predicted high levels of VEGF-A [OR = 1.025 (95%CI: 1.004–1.047), PFDR = 0.060] and VEGF-D [OR = 1.080 (95%CI: 1.039–1.123), PFDR = 0.001]] were associated with an increased risk of atrial fibrillation, while no causal relationship was observed between VEGF-C (PFDR = 0.419), VEGFR-2 (PFDR = 0.784), and VEGFR-3 (PFDR = 0.899) and atrial fibrillation risk. Moreover, only genetically predicted high levels of VEGF-D [OR = 1.071 (95%CI: 1.014–1.132), PFDR = 0.087] increased the risk of atrial fibrillation and flutter. Sensitivity analysis demonstrated that the relationship between VEGF-D levels and the risk of atrial fibrillation was robust. Conclusion This study supports a causal association between high VEGF-D levels and increased risk of atrial fibrillation.